Serum Vitamin D Concentration and Potential Risk Factors for its Deficiency in HIV Positive Individuals - Etminani-Esfahani, Maryam; Khalili, Hossein; Soleimani, Nahid; Jafari, Sirous; Abdollahi, Alireza; Khazaeipour, Zahra; Gholami, Kheirollah (Current HIV Research, 2012)
Human immunodeficiency virus (HIV) infected individuals are prone to malnutrition, and deficiencies of some minerals and vitamins. The aim of this study is to evaluate the frequency of vitamin D deficiency and determine the possible risk factors associated with this problem in HIV-infected individuals. This cross-sectional study was performed on 98 adult patients referred to the Emam Khomeini Hospital Complex, Tehran, Iran. The patients' serum vitamin D concentration was determined using radioimmunoassay method. The possible correlations between demographic and clinical data with the level of vitamin D were evaluated. Vitamin D levels less than 35 nmol/l were considered as deficient in this study. Eighty-five (86.7%) of the patients had serum vitamin D deficiency (concentrations less than 35 nmol/l) in this study. Coinfection with hepatitis C virus (HCV) was present in 54 (55.1%) of the patients. Only daily intake of vitamin D (r=0.304, p=0.002), duration of sun exposure (r=0.268, p=0.009), the level of PTH (r=-0.459, p<0.001), daily intake of calcium (r=0.239, p=s0.018) and GFR of more than 90 ml/min (OR=1.208, CI 95%= 1.080-1.350, p=0.033) had a correlation with serum vitamin D concentration. Being female (OR=7.224, CI 95%= 3.640-14.335, p<0.001), unemployed (OR= 1.627, CI 95%=1.209-2.190, p<0.001) and infected with HCV (OR= 1.811, CI 95%= 1.331-2.465, p<0.001) were related to the severe serum vitamin D deficiency. Vitamin D deficiency is a common problem in Iranian HIV-infected patients and with concern of this vitamin's important role in health issues, early evaluation of its status and providing appropriate nutritional support seems to be important.
Keywords: GFR